Determination of Vitamins, Trace Elements, and Phytochemical Compounds in Boswellia Carterii Leaves Extracts - Heyam A. Hashim; Mustafa T. Mohammed; Mohammed Z. Thani; Nisred K. Klichkhanov (Al-Mustansiriyah Journal of Science)
Background: The assessment of the extraction yield and nutritional content of Boswellia carterii extracts, including vitamins and trace elements, is significant. Objective: The study aims to identify phytochemical compounds present, and concluding on the plant’s potential health benefits and dietary contributions. Methods: The present study was conducted to extract the vitamins, trace elements and phytochemical constituents of Boswellia carterii leaves extracts using distilled water, ETOH (99%), and Ethylacetate by soxhlet. The yield of extracts was (18.361g/100g distilled water) while (29.322g/100g ETOH) and the Ethylacetate was found to be (27. 312g/100g). Different types of vitamins were estimated in all extracts utilizing HPLC. Results: Vitamins showed interesting results by revealing (A, B6, and B12). Vita. B12 is the most abundant in Alcohol extract, whereas vita. B12 is the most abundant in aqueous extract, and vita. B12 is the most abundant in ethylacetate compared with vitamin A, and B6. These findings call for more research into the vitamins in Boswellia carterii and their antioxidant relevance in therapeutic herbal medicine. Different metal ions were measured using FAAS (Cd, Co, Cr, Cu, Mn, Ni, Pb, Se, and Zn). The results of the qualitative detection of all extracts indicated the existence of Alkaloids, Steroids, Terpenes, Phenols, Carbohydrates, Glycosides, Proteins, Saponins, Tannins, and Flavonoids. Conclusions: The results of the qualitative detection of all extracts indicated the existence of Alkaloids, Steroids, Terpenes, Phenols, Carbohydrates, Glycosides, Proteins, Saponins, Tannins, and Flavonoids.